Next‐generation Bruton's tyrosine kinase inhibitor BIIB091 selectively and potently inhibits B cell and Fc receptor signaling and downstream functions in B cells and myeloid cells. Issue 6 (14th June 2021) - Bame, Eris; Tang, Hao; Burns, Jeremy C; Arefayene, Million; Michelsen, Klaus; Ma, Bin; Marx, Isaac; Prince, Robin; Roach, Allie M; Poreci, Urjana; Donaldson, Douglas; Cullen, Patrick; et al.
Abstract: Objectives: Bruton's tyrosine kinase (BTK) plays a non‐redundant signaling role downstream of the B‐cell receptor (BCR) in B cells and the receptors for the Fc region of immunoglobulins (FcR) in myeloid cells. Here, we characterise BIIB091, a novel, potent, selective and reversible small‐molecule inhibitor of BTK. Methods: BIIB091 was evaluated in vitro and in vivo in preclinical models and in phase 1 clinical trial. Results: In vitro, BIIB091 potently inhibited BTK‐dependent proximal signaling and distal functional responses in both B cells and myeloid cells with IC50 s ranging from 3 to 106 nm, including antigen presentation to T cells, a key mechanism of action thought to be underlying the efficacy of B cell‐targeted therapeutics in multiple sclerosis. BIIB091 effectively sequestered tyrosine 551 in the kinase pocket by forming long‐lived complexes with BTK with t 1/2 of more than 40 min, thereby preventing its phosphorylation by upstream kinases. As a key differentiating feature of BIIB091, this property explains the very potent whole blood IC50 s of 87 and 106 nm observed with stimulated B cells and myeloid cells, respectively. In vivo, BIIB091 blocked B‐cell activation, antibody production and germinal center differentiation. In phase 1 healthy volunteer trial, BIIB091 inhibited naïve and unswitched memory B‐cell activation, with an in vivo IC50 of 55 nm and without significant impact on lymphoid or myeloid cell survival after 14 days of dosing. Conclusion: Pharmacodynamic results obtained in preclinical and early clinical settings support the advancement of BIIB091 in phase 2 clinical trials. Abstract : In this study, we characterise BIIB091, a novel, potent, selective and reversible small‐molecule inhibitor of Bruton's Tyrosine Kinase (BTK). In vitro, BIIB091‐inhibited BTK‐dependent proximal signaling and distal functional responses in both B cells and myeloid cells, including antigen presentation to T cells, a key mechanism of action thought to be underlying the efficacy of B cell‐targeted therapeutics in MS. In vivo, BIIB091 blocked B‐cell activation, antibody production and germinal center differentiation, however in phase 1 healthy volunteer study, BIIB091 inhibited B‐cell receptor‐mediated activation of naïve and unswitched memory B cells.